Investigação molecular de patógenos em morcegos coletados no estado do Mato Grosso, Brasil - Pereira, Nathalia de Assis (2024)
Bats can harbor a wide variety of microorganisms, including viruses, bacteria, fungi and protozoa, and several factors contribute to their being carriers and disseminators of potentially zoonotic pathogens, such as the ability to make long flights, ease in adapting to the most diverse environments, close contact with humans and domestic animals in urban areas, longevity and reduced susceptibility to various human and animal pathogens, remaining asymptomatic most of the time. In this study, an molecular investigation was carried out on some zoonotic pathogens transmitted by bats, namely: Bartonella spp., Mycoplasma spp., Trypanosoma spp. and Histoplasma capsulatum. Bats of different species were captured in 5 municipalities in different regions of Mato Grosso (Cuiabá, Santo Antônio do Leverger, Nobres, Poconé and Barão de Melgaço), and the samples obtained from these animals were subjected to a qPCR. The results of these molecular analyzes demonstrated positive samples for the genus Mycoplasma spp. in bats of the species Glossophaga soricina, Molossus sp., Desmodus rotundus. The State of Mato Grosso has a great diversity of bat species, and this study demonstrated the presence of a zoonotic pathogen in the specimens sampled. Therefore, it is essential to elucidate the distribution of these hosts in this region to facilitate the implementation of effective surveillance against the pathogens in the study adressed.